Micro-screw extrusion 3D printing of multiscale ternary nanocomposite absorbers – Part I: Comprehensive materials characterization and exceptional microwave absorption performance - Jiahang Zhang; Dongsheng Li; Mingming Wang (Materials & Design)
In the context of structural-functional integration, developing advanced microwave-absorbing resin-based composites is an effective solution to combat electromagnetic pollution in military and civilian applications. The use of nanofillers in immiscible polymer blends has gained significant attention for their superior performance. This research employs micro-screw extrusion 3D printing to create a ternary nanocomposite with multi-walled carbon nanotubes, featuring a multi-scale structure and excellent microwave absorption. Nylon 12 and polypropylene serve as matrix materials. By adjusting the geometric structure and component ratios, efficient electromagnetic wave absorption is achieved. Results show that the selective distribution of MWCNTs enhances the composite’s conductivity and dielectric properties. The screw extrusion process proves advantageous for mass production, multi-material compatibility, and online blending, highlighting the nanocomposite’s potential for electromagnetic wave stealth, shielding, and flexible sensing applications.